2010
DOI: 10.1016/j.fertnstert.2008.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Short-term hormone treatment modulates emotion response circuitry in postmenopausal women

Abstract: Objective-To study the effects of combination hormone therapy (HT) on emotional processing in postmenopausal women using functional neuroimaging.Design-A randomized, double-blind placebo-controlled cross-over study was performed.Setting-A tertiary care university medical center.Participants-Ten healthy postmenopausal women (mean age 56.9 years, S.D. = 1.4) were recruited.Interventions-Women were randomized to the order they received combined hormone therapy, 5 ug ethinyl estradiol and 1 mg norethindrone acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
2
16
0
Order By: Relevance
“…Estradiol receptors are located in a number of brain areas, including regions important for the autonomic, hormonal, and cognitive-emotional response to psychosocial stress (Love et al, 2010). The relation of stress to depression onset (Frank et al, 1994; Kendler et al, 1999; Kendler et al, 2000) and the altered function of the stress system in major depression (Burke et al, 2005; Lupien et al, 2009) suggest that modulation of the psychosocial stress response may be a mechanism through which estradiol fluctuation may contribute to MDD and PTSD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol receptors are located in a number of brain areas, including regions important for the autonomic, hormonal, and cognitive-emotional response to psychosocial stress (Love et al, 2010). The relation of stress to depression onset (Frank et al, 1994; Kendler et al, 1999; Kendler et al, 2000) and the altered function of the stress system in major depression (Burke et al, 2005; Lupien et al, 2009) suggest that modulation of the psychosocial stress response may be a mechanism through which estradiol fluctuation may contribute to MDD and PTSD risk.…”
Section: Discussionmentioning
confidence: 99%
“…To examine brain activation during emotional processing, subjects viewed emotional pictures from the International Affective Picture System (IAPS)[28] and rated each picture while in the MRI scanner as positive (pleasant), neutral, or negative (unpleasant) using a button press[29]. Subjects viewed sixty-four pictures from each emotional category, chosen from this set of pictures based on their affective rating by a normative female sample.…”
Section: Methodsmentioning
confidence: 99%
“…Neuroimaging studies of emotion processing in menopausal women are essentially lacking, and findings are thus far inconclusive (Table 6 ). A randomized placebo-controlled cross-over study including ten postmenopausal women portrayed an increased activation, though in different regions, during negative emotional stimuli processing, in both the placebo and estrogen-progestagen treated groups, and higher activation of the left medial frontal cortex during positive stimuli processing in the placebo group (Love et al, 2010 ). Later, a larger cross-sectional study of long-term HRT users also showed puzzling activation in estrogen treated women and non-users, and in current vs. past HRT users (Shafir et al, 2012 ).…”
Section: State-of-the-artmentioning
confidence: 99%
“…Later, a larger cross-sectional study of long-term HRT users also showed puzzling activation in estrogen treated women and non-users, and in current vs. past HRT users (Shafir et al, 2012 ). While Love et al found no effect on performance of the task (Love et al, 2010 ), Shafir et al found a slower response time in HRT users, but higher accuracy in picture rating among current users compared to past users (Shafir et al, 2012 ). In addition, greater regional activity in the dorsal lateral prefrontal cortex during high conflict resolution was found in one study investigating emotion regulation in eleven peri- and postmenopausal women (Frey et al, 2010 ).…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation